Primary Sjogren syndrome diagnosed simultaneously with localized amyloidosis of the lacrimal gland: A case report. Issue 23 (June 2018) - Kweon, Seong-Min; Koh, Jung Hee; Lee, Han-Na; Kim, Eunsung; So, Min Wook; Shin, Ho-Jin; Young Choi, Hee; Lee, Seung-Geun
Abstract: Introduction: Amyloidosis accompanied by Sjögren's syndrome (SS) has been reported to occur primarily in the skin, lungs, tongue, and mammary gland. However, SS in association with secondary amyloidosis is rarely reported, and knowledge of its relevance is inadequate. Here we report a case of primary SS diagnosed simultaneously with localized amyloidosis of the lacrimal gland. Case presentation: A 45-year-old woman complaining of a left eyelid mass was referred to the hospital and was diagnosed with localized amyloidosis after excisional biopsy. She was then referred to the rheumatology department for additional evaluation for amyloidosis. Subsequently, her diagnosis was primary SS based on the presented symptoms and results of the Schirmer test, serologic testing, and minor salivary gland biopsy. Pilocarpine (10 mg/d) and hydroxychloroquine (200 mg/d) were initiated for the treatment of SS. Six months after the initial diagnosis, the dry eyes and mouth did not worsen and no masses suggestive of localized amyloidosis were reported. Conclusion: This is a rare case of amyloidosis, localized to the lacrimal gland, with SS. Therefore, despite its rarity, physicians should be aware of the potential coexistence of secondary amyloidosis, even in the localized form, in patients with SS.